Supporting Parents’ Needs as Educational Partners to Enhance Children’s Classroom Learning - Denise Miller; Roy Venketsamy (Profesi Pendidikan Dasar, 2022)
Parents are essential in supporting their children's learning and development. Parental support to young learners include helping their children with homework, school projects, collaborating with the teachers, participating in school events and school governance. This study argues for strengthening an inclusive home-school partnership to effectively support their learners. The focus of this study was to explore the parents-school partnership in supporting children's learning. The research applied a qualitative approach using a semi-structured online interview questionnaire via Google forms. Fourteen (14) parents met the inclusion criteria, and interview forms were used in the analysis. The study found that most South African parents have minimal knowledge and understanding of how to support their children’s learning. There is a lack of communication and partnership between the school and home. This will ensure appropriate communication and participation of parents in the school activities. Schools should recognise that the South African context is diverse and should be inclusive in their policies to accommodate all parents. School governing bodies should be enabled to foster the relationship between the schools and parents since they are representative of the parents. The results showed that to strengthen the home-school partnership, schools must be conscious of applying principles that will advocate for inclusiveness and the recognition of the diversity of the parent population.